Skeletal indicators of locomotor adaptations in shrews - Woodman, Neal (THERYA, 2023)
The Soricidae (Mammalia: Eulypotyphla) comprises more than 450 species inhabiting a variety of habitats on five continents. As a family, shrews employ a variety of locomotor modes that incorporate ambulatory, fossorial, aquatic, and scansorial behaviors, illustrating an ability to exploit a variety of natural substrates and their associated resources. In this study, the association of skeletal morphology and three of the dominant locomotor modes in the family—ambulatory, semi-fossorial, and semi-aquatic behaviors—was investigated in up to 52 species of 12 genera representing all three subfamilies of Soricidae. From skeletal measures, 34 morphological indices were calculated, most of which have been used previously to characterize substrate use among shrews, rodents, and other mammals, and analyzed for their individual effectiveness for discriminating the three locomotory modes. To assess their effectiveness in combination, subsets of locomotor indices were analyzed using 1) mean percentile ranks, 2) the first principal component from principal components analysis, and 3) plots and classifications from discriminant function analyses. In general, the three methods effectively identified and grouped the three locomotor modes and identified smaller subsets. Additional analyses were then used to classify the locomotor behaviors of five species whose locomotor modes were unknown or ambiguous. The analyses reinforce and broaden the scope of a previously identified observation of the wide range of grades of morphological variation that may permit an equally diverse range of locomotor abilities among the Soricidae.